Plan de negocio para la creación de una nueva línea de negocio en la empresa Metrocuadrado CIA. LTDA., enfocada en la creación de un proyecto habitacional en la Urb. Jardines de Amagasí en Quito - Jaramillo Gordillo, Carlos Alberto (2020)
Metrocuadrado Cía. Ltda. Is a company that provides construction services for public and private entities, due to the economic crisis in the country, the current business of the company is not yielding the expected results, that is why the creation of a new line is proposed of business in the company Metrocuadrado Cía. Ltda. Focused on the creation of a housing project in Jardines de Amagasí in Quito. The SHYRA building is a project to be carried out in the Urb. Jardines de Amagasí, the same one that is located in the El Inca parish, north center of the city of Quito and is made up of 12 housing units distributed over 6 floors, with a footage range between 87.65 and 107.49 m2. The following business plan seeks to determine the financial viability of the project, through the analysis of several important components such as the macroeconomic environment, the market study, the location of the project, the description of the project, its cost analysis, its promotion and its financial study with which we will have a clear idea if the project will meet the general objective.